Welfare reforms and labour supply in Italy - Institute for Labour Market Policy Evaluation, Uppsala; Brugiavini, Agar (Uppsala, 2009)
"This paper looks at welfare reforms in Italy and their effects on labour supply. I focus on social security reforms, which have taken place in the 1990s and on labour market reforms. Old age social security expenditure in Italy is high (14% of GDP) and the system has been very generous on early retirement possibilities: the reforms have tried to tackle these issues with mixed results. The labour market reforms have addressed the rigidity of the labour market by making it easier for firms to hire on a short-term basis. However the UI system is limited to open-ended contracts and coverage is also restricted, so that young workers employed in short-term contracts have very little protection from the welfare state."